A13: The Research in Arthritis in Canadian Children Emphasizing Outcomes (ReACCh Out) Cohort: Prospective Determination of the Incidence of New Onset Uveitis in Juvenile Idiopathic Arthritis. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Watanabe Duffy, Karen N; Lee, Jennifer; Guzman, Jaime; Barrowman, Nick; Morishita, Kimberly; Spiegel, Lynn R.; Stringer, Elizabeth; Gibbon, Michele; Yeung, Rae SM; Tucker, Lori B.; Oen, Kiem; Duffy, Ciarán M.; et al.
Abstract : Background/Purpose: Previous studies of uveitis in Juvenile Idiopathic Arthritis (JIA) patients have reported prevalence and not incidence. The ReACCh Out cohort, a large inception cohort of newly diagnosed JIA patients provided the opportunity to prospectively ascertain the true incidence of new onset uveitis. The objectives of this study were to determine the overall incidence rate and its trajectory over time. Methods: ReACCh Out recruited newly diagnosed JIA patients between January 2005 and December 2010, from 16 Canadian centres across the country. Prospective data was collected every 6 months for the first 2 years, then yearly. Data was collected on numerous clinical and laboratory measures including the diagnosis of uveitis and its complications, determined by an ophthalmologist. A Poisson model was used to estimate the overall incidence rate. A Kaplan‐Meier plot was used to evaluate the time from diagnosis of JIA to the time of diagnosis of new onset uveitis. Results: 1104 patients with newly diagnosed (≤6 months) JIA with ≥1 follow‐up visit were reviewed. Patients were predominantly female (63%), age at diagnosis was 9.3 (3.9, 13.0) years. Time from diagnosis to enrollment was 0.3 (0, 1.6) months. Follow‐up to last visit or study end was 34.2 (21.5, 48) months. 23 patients whose uveitis status was not available, were excluded. 77 patients with new onset uveitis were identified during the study period. The overall incidence rate of new cases of uveitis following the diagnosis of JIA was 2.9% per year (95% confidence interval 2.3–3.6). Following the trajectory of new cases of uveitis over time, the incidence of new cases showed a slow decline over time (Figure1 ). Importantly, new cases of uveitis occurred as far out from diagnosis as the end of the study period. Kaplan‐Meier plots were also used to evaluate age at diagnosis of new onset uveitis and gender. Results support previously identified risk factors for uveitis including younger age (<5 years) and female gender. The frequency of uveitis occurred in the JIA patients in the following distribution according to subtype: oligoarthritis (43, 56%), polyarthritis RF negative (18, 23%), polyarthritis RF positive (1, 1%), psoriatic (4, 5%), ERA (1, 1%), systemic (1, 1%) and undifferentiated (9, 12%). Conclusion: In a large inception cohort of newly diagnosed JIA patients followed prospectively, the overall incidence rate of new cases of uveitis was 2.9% per year. The slow decrease in incidence over time and the development of new cases of uveitis years later, highlight the importance of ongoing and long term surveillance.